Komparasi Prestasi Belajar Matematika antara Siswa yang diajar menggunakan Model Pembelajaran Kooperatif tipe Snowball Throwing dan Tipe Make a Match di Kelas VII SMP - Tahir; Hamzah Upu; Suradi (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2019)
This research was conducted to determine the comparison of student learning achievement through the application of the cooperative model type Snowball Throwing and Make a Match in mathematics learning. This research was an experimental research involving two groups treated with research sample of 47 students from class VII SMP Sinjai selected by using the double cluster random sampling technique. Techniques of collecting data using instruments: (1) observation sheet of learning model implementation and (2) tests of mathematics learning result.Data were analyzed with descriptive statistics and inferential statistics with t-test analysis. The results showed that : (1) Average score of mathematics learning achievement of 25 students after learning using the Snowball Throwing type of cooperative learning model which is 4% in the very low category, 40% in the medium category, 36% in the high category and 20% in the very high category. (2) The average score of mathematics learning achievement from 22 students after learning using the Make a Match type of learning model is 9.09% in the very low category, 4.54% in the low category, 50% in the medium category and 18, 18% in the high and very high categories. (3) There is no significant difference between student achievement after applying the snowball throwing type cooperative learning model and the type of make a match in Class VII Junior High School with the Rectangular Build Up material.